Cost‐effectiveness of laparoscopic fundoplication versus continued medical management for the treatment of gastro‐oesophageal reflux disease based on long‐term follow‐up of the REFLUX trial. Issue 9 (17th June 2013) - Faria, R.; Bojke, L.; Epstein, D.; Corbacho, B.; Sculpher, M.; ,
Abstract : Background: Laparoscopic fundoplication surgery has been shown to be a cost‐effective alternative to continued medical management over 1 year for patients with gastro‐oesophageal reflux disease (GORD). The longer‐term cost‐effectiveness is, however, uncertain. This study evaluated the long‐term health benefits, costs and cost‐effectiveness of laparoscopic fundoplication compared with continued medical management in patients with GORD. Methods: Individual patient data were used from the 5‐year follow‐up of the REFLUX trial, a large multicentre, pragmatic, randomized trial in which 357 patients with GORD for at least 12 months at trial entry were allocated randomly to early laparoscopic fundoplication or continued medical management. Health outcomes were expressed in quality‐adjusted life‐years (QALYs). A UK National Health Service perspective was used for costs. Results: The group randomized to surgery experienced better health outcomes in each year of follow‐up, but the difference narrowed over time. At 5 years, the surgery group had experienced 0·216 (95 per cent confidence interval 0·021 to 0·412) more QALYs but also accrued €1832 (1214 to 2448) more costs. The incremental cost‐effectiveness ratio was €8481 per QALY gained. The probability that surgery is the most cost‐effective intervention was 0·932 at a threshold of €24 134/QALY (£20 000/QALY). Results were robust to most sensitivity analyses, except where patients with missing data randomized to surgery were assumed to have worse health outcomes. Conclusion: Laparoscopic fundoplication is a cost‐effective alternative to continued medical management over 5 years. No evidence was found to suggest that the cost‐effectiveness of laparoscopic fundoplication diminishes over time. Abstract : Supports greater use of surgery rather than medical therapy